Errors in Writing the Sequence of the Letters 汉字 [hànzì] by Class XI IBB Students at SMA Nurul Jadid Paiton Probolinggo - Habibatul Karimah, Erina; Bukhori, Herri Akhmad; Mardasari, Octi Rjeky (Journal of Chinese Language and Culture Studies, 2023)
Writing 汉字 [hànzì] has a fairly high level of difficulty because it has rules for writing in the letters. Students rarely write the letters 汉字 [hànzì] according to the rules for writing the stroke order. This study aims to describe the forms of errors in writing the stroke order of the letters 汉字 [hànzì] by students of class XI IBB SMA Nurul Jadid Paiton Probolinggo and describe the factors that cause errors in writing the stroke order of letters 汉字 [hànzì]. This study used descriptive qualitative method. The research instruments used were tests and questionnaires filled in by 22 students of class XI IBB SMA Nurul Jadid Paiton Probolinggo. The results show that students still make many mistakes when writing the letters [hànzì], especially in the order of the strokes. Factors that cause students to make mistakes are because students have not mastered the material related to writing the letters 汉字 [hànzì], students have not been able to distinguish between basic and compound strokes, forget the order of writing the letters 汉字 [hànzì], lack of concentration and thoroughness when working on questions.